An N-Terminal Molecular Form of Parathyroid Hormone (PTH) Distinct from hPTH(1–84) Is Overproduced in Parathyroid Carcinoma - Mishaela R. Rubin; Shonni J. Silverberg; P D'Amour; Jean‐Hugues Brossard; Louise Rousseau; James Sliney; Tom Cantor; John P. Bilezikian (2007)
Abstract Background: A new parathyroid hormone (PTH) species, the N-terminal PTH form (N-PTH), is distinct from intact human PTH of 84 amino acid residues [hPTH(1–84)] and is recognized in a 3rd-generation assay of “whole” PTH (wPTH; the 1–2 epitope) but not in a 2nd-generation assay of “total” PTH (tPTH; the 12–18 epitope). N-PTH usually represents <15% of wPTH but can be overproduced in severe primary hyperparathyroidism (PHPT) and secondary hyperparathyroidism. We investigated whether N-PTH is also overproduced in parathyroid cancer and whether N-PTH concentration is influenced by calcimimetic therapy. Methods: We studied 8 patients with parathyroid carcinoma before and at week 16 of cinacalcet therapy, 6 patients with PHPT, and 6 control individuals. We fractionated sera with HPLC and analyzed fractions with the 2 assays to quantify hPTH(1–84), N-PTH, and non-(1–84) PTH fragments. Results: Half of parathyroid carcinoma patients had an increased wPTH:tPTH ratio [mean (SD), 1.35 (0.29)]; the others had a typical ratio [0.72 (0.12)]. HPLC fractionation of sera from 2 high-ratio patients confirmed N-PTH overproduction [65% (12%) of wPTH]. The N-PTH fraction was <15% of wPTH in PHPT and healthy individuals. Calcimimetic therapy appreciably reduced calcium concentrations in parathyroid carcinoma patients but had little influence on PTH concentration, the wPTH:tPTH ratio, or the PTH HPLC profile. Conclusion: N-PTH is overproduced in some parathyroid cancer patients, but calcimimetic therapy does not influence its production. The clinical implications of this finding in parathyroid carcinoma await additional studies with an emphasis on N-PTH’s biological activity and with larger numbers of patients.